3 - Relation adolescent-adolescente au Cameroun : le « sexuel » comme moyen d’expression - Noumbissie, Claude Désiré (Africa Development, 2021)
To observe closely the behavior of the teenagers these last years, it is very likely to notice an omnipresence of the sexual there. Indeed, they get dressed sexy, use a sexual language and have premature, frequent sexual practices and at risk. The psychosocial look which we carried its, allowed us to understand(include) that this omnipresence of the sexual in the adolescent behavior is not only the simple fact of the puberty and the sexual awakening in the adolescence but also testifies of a concern(marigold) of domination, of submission or ownership. The analysis of the results (profits) of individual interviews and focuses group discussion, allowed us to notice on one hand that in the relations teenager (boy) – teenager (girl) the sexual is used as means of expression of power through the language, the clothing style and the sexual practices there; and on the other hand that the girls more make use of it than the boys.